VIOLENCE AGAINST WOMEN: A COMPARATIVE ANALYSIS OF LEGAL PROTECTION DEVICES BETWEEN BRAZIL AND THE UNITED STATES - da Silva Candeia, Acilina; Paula Moreira Alves Lázaro, Anna (Revista Gênero e Interdisciplinaridade, 2024)
The general objective of this study is to analyze the legal provisions to combat violence against women through a comparative analysis between Brazil and the United States. Regarding the methodology proposed in this study, it can be said that it will be bibliographical, considering that articles, magazines, dissertations and other studies that deal with this issue were used as a source of research and theoretical basis. of this study. The Maria da Penha Law and the Violence Against Women Law play different roles in the legal systems of their respective countries, however, it appears that both laws, when analyzed as individual entities within their own legal frameworks (Brazil and the United States) , were pioneering efforts against domestic violence. The importance of these laws cannot be overstated: they were the first steps taken by their nations to address these issues and have intrinsic value in defending women's rights, promoting the dignity and protection of women.